Islanding detection of interconnected grids based on synchrophasor measurements (PMU) - Mukhopadhyay P.; Patil S.; Rajkumar A.; Chitturi S.; Kumar C.; Jain A.; Gupta S. (My University, 2025)
This paper deals with the development of algorithm for islanding detection of Interconnected Grids as a result of Loss of interconnecting transmission line(s). The algorithm must also be able to segregate between the cases of islanding and cases of Loss of Parallel Feeder (LOPF), Generation Trip, and Load Trip. The new method uses 3 phase synchronized measurements obtained from Phasor Measurement Units (PMUs) for the detection of unbalanced islanding of Interconnected Grids. The model developed is simulated on two Area-two machine System in SIMULINK Environment. Furthermore, the algorithm is verified and tested on actual case study for the loss of the synchronization between NEW and SR grid of India. © 2014 IEEE.